Morningness–Eveningness and College Advising: A Road to Student Success?. Issue 4 (December 2014) - Schulke, Beverly Brown; Zimmermann, Laura K.
ABSTRACT In addressing the challenges faced by E‐type (evening‐type) students, researchers have pointed to the need for school schedules that reflect chronotypic concerns and the recognition of the importance of sleep for academic achievement and well‐being. One approach to dealing with this issue for adolescent students has been to move the start of the school day later. In college, however, schedules become more varied and the social context in which these challenges occur differs requiring more individualized approaches to scheduling. In spite of this, morningness–eveningness is rarely considered by college administrators, advisors, or individuals involved in student services. It is important that faculty and staff who work with students be aware of chronotypical influences on classroom performance and other aspects of student life so that they can help them succeed in college and beyond.